ANALYSIS OF ADDED VALUE AT UD. COCONUT INDUSTRY IN GAMPONG COT PUUK KECAMATAN GANDAPURA KABUPATEN BIREUEN (Case Study: Coconut Gongseng Inkego U Seu Neulheu) - Mirza Arianda; Riani; Emmia Tambarta Kembarten (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This research was conducted in Gandapura District, Bireuen Regency. The purpose of this study was to find out how the Analysis of Added Value at UD Coconut Industry in Gampong Cot Puuk, Gandapura District, Bireuen Regency (Case Study: Kelapa Gongseng Inkego (U Seu Neulheu). This study used a quantitative descriptive method. The results showed that the benefits obtained in depth once the production process at UD Coconut industry was Rp. 6,249,177. The added value obtained by coarse gongseng coconut was Rp. 2,036/kg obtained by coarse gongseng coconut is Rp. 877/kg with a profit rate of 43%, while the added value obtained from refined coconut gongseng is Rp. 12,213/kg with a profit rate of 91%.